Performance of Boro rice cv. BRRI dhan28 as influenced by different plant establishment methods and weeding regimes - Kabiraj, Md Sojib; Rashid, Md Mamunur; Anwar, Md Parvez; Hossain, Md Delwar (Journal of the Bangladesh Agricultural University, 2024)
At present time food safety is a precedence issues in Bangladesh and it is essential to increase the production level of rice to address this mission. The study was undertaken to evaluate the yield performance of boro rice cv. BRRI dhan28 under different plant establishment methods and weeding regimes. The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during December 2017 to June 2018. It was a two factor experiment that comprehended three plant establishment methods viz. sprouted seeds in line, sprouted seeds in broadcasting and transplanting of seedlings in line; five weeding regimes viz. no weeding, one hand weeding at 20 day after planting (DAP), two hand weeding at 20 and 40 DAP, three hand weeding at 20, 40 and 60 DAP, and application of herbicide (Sathi 10WP @ 185 g ha-1). The experiment was set up following randomized complete block design with three replications. Yield contributing characters and yield of Boro rice were exerted significantly by plant establishment methods and the highest results were recorded in transplanting of seedlings in line method in which the number of total tiller hill-1 (6.39), number of effective tiller hill-1 (5.93), grains panicle-1 (99.28), 1000 grain weight (24.16 g) and grain yield (4.19 t ha-1). And the lowest results were found in sprouted seeds in broadcasting method. Considering weeding regimes, the highest number of total tillers hill-1 (6.03), effective tillers hill-1 (5.28), grains panicle-1 (101.4), grain yield (4.12 t ha-1) and straw yield (5.74 t ha-1) were recorded with application of herbicide method. Contrariwise, no weeding showed the lowest values. In interaction effect, maximum grain yield (4.48 t ha-1) was obtained in transplanting of seedlings in line method with application of herbicide and Sprouted seeds in broadcasting method with no weeding was performed the lowest grain yield (2.86 t ha-1). From the overall results, the growers can be recommended to cultivate boro rice cv. BRRI dhan28 in transplanting of seedlings in line method with application of herbicide at different Agro-ecological zones of Bangladesh. J Bangladesh Agril Univ 18(4): 934–940, 2020 https://doi.org/10.5455/JBAU.129791